Universal Design: Beyond Usability And Aesthetic Studies For Prayer Chair - Musdi, Shanat; Mohammad, Jaidi Kumalah (UNIMAS Publisher, 2018)
User-usability effect and aesthetic recognizes to fortify value in product creation in assisting the product to be more valuable. The contribution of usability and aesthetic factors enable to increase the potency of the product to be utilized for the target market segment of individual preferences. This paper focuses on the design aspect concerning the aesthetic-usability effect. An appropriate technique of designing the product, which compromises by many types of users in retaining the functionality, size, proportion, space for approach, reach manipulation, is discussed. Performing a prayer using a chair is a critical necessity for those who are no longer able to stand for a longer period of time. Little attention is given to these issues is the main caused of neglected targets for their comfort in the practices of prayed. The researchers agreed that the pleasant appearance of the products able to contribute to positive aesthetic-usability feeling and serve affordance quality with end-users, comparable to less aesthetic outlooks.